MAVS is important for antiviral defense against influenza A virus in a human respiratory epithelium model - Maja Hemberg; Anne Louise Hansen; Jacob Storgaard; Julia Blay-Cadanet; Alice Pedersen; Anne Laugaard Thielke; Christian Kanstrup Holm (PLoS ONE, 2026)
The respiratory epithelium is an important immunological barrier and the first line of defense against influenza A virus (IAV). In mice and in various cellular systems, induction of type I interferons (IFNα/β) during IAV infections is known to depend on cytosolic RNA sensors retinoic acid-induced gene I (RIG-I) and melanoma differentiation-association gene 5 (MDA5) and their common adaptor protein mitochondrial antiviral-signaling adaptor protein (MAVS). Until now, it has not been possible to directly assess the importance of MAVS for induction of IFNs and for resistance to IAV infection in primary human respiratory epithelium. Here, we used CRISPR-Cas9 to establish MAVS-deficient cultures of primary human respiratory epithelium using the air-liquid interphase culture system. Using this setup, we show that MAVS is indeed required for the induction of type I and type III IFNs and subsequently for the induction of IFN-stimulated genes in response to IAV infection in this respiratory epithelium model. Finally, we demonstrate that MAVS is important for restricting viral replication in this model. In conclusion, this study demonstrates that MAVS plays a non-redundant protective role during IAV infection in primary human respiratory epithelium.